Die Lehre, der Weg und die namenlose Religion: Mögliche Äquivalente eines Religionsbegriffs in der tibetischen Kultur - Roesler, U (Acta Universitatis Upsaliensis, 2013)
Summary in English: The Tibetan language has several words that are similar to, but not identical with the word “religion”, the closest equivalents being chos and chos lugs. However, on the one hand chos became particularly closely linked with Buddhism, and on the other hand composite expressions with chos can also be used for the secular order of society. For both reasons the word is no exact equivalent of “religion”. The article explores the Tibetan vocabulary for religious doctrine, religious practice, various religious groups, and religion as opposed to the secular sphere. It then analyses several passages from Tibetan works and argues that religions are perceived and described as competing, but therefore also analogous phenomena. It therefore seems justified to say that – even without an exact lexical equivalent – Tibetan authors have an implicit concept of “religion” that could be described in terms of Wittgenstein’s “family resemblances”.